KAJIAN YURIDIS TERHADAP KEGIATAN JUAL BELI PAKAIAN BEKAS MENURUT HUKUM POSITIF DI INDONESIA - RODY AHMAD TOYIB; Hera Alvina Satriawan (Private Law, 2023)
This study's purpose is to determine the legal protection for users of used clothing and the type of responsibility of used clothing sellers to consumers. This type of research is normative-empirical legal research with statute approaches, conceptual approaches, and sociological approaches. The types of legal materials use primary legal materials and secondary legal materials. Analysis of legal materials uses descriptive qualitative. Act Number 7 of 2014 concerning Trade says Importers are required to import goods or clothing in a new condition. Used clothing traders at the Karang Sukun Market are only responsible for the compensation for damaged clothing, but for consumers who have health problems, traders are not responsible.